The dust production rate of carbon-rich stars in the Magellanic Clouds. Issue Volume 14:Issue S343(2019) (August 2018) - Nanni, Ambra; Groenewegen, Martin A. T.; Aringer, Bernhard; Marigo, Paola; Rubele, Stefano; Bressan, Alessandro
Abstract: We present our new investigation aimed to estimate the mass-loss and dust production rates of carbon-rich stars (C-stars) in the Magellanic Clouds (MCs). We compute dust growth and radiative transfer in circumstellar envelopes of C-stars for a grid of stellar parameters and for selected optical constants that simultaneously reproduce the main colour–colour diagrams in the infrared. We employ these grids of spectra to fit the spectral energy distribution of C-stars in the MCs. We find that our estimates can be significantly different from the other ones in the literature.